The manufacture of medical and health products by transgenic plants - Galun, Esra, 1927-2014 (Imperial College Press ; Distributed by World Scientific Pub. Co., 2001)
In the mid-eighties, there was a revolution in plant biotechnology. Simple procedures could be used to genetically transform plants. Such transgenic plants will express alien genes, virtually from any organism, provided the genes are flanked by appropriate controlling elements. Soon after this biotechnology became available, there was an awareness that crop plants can serve as manufacturers of high-value medical products. This book provides the molecular and biotechnological background for genetic transformation in plants, as well as updated information about the production of antibodies, antigens and other medical and health products by transgenic plants. The book handles the relevant information in a critical manner by pointing out the risks and problems as well as presenting the outlook for development in this field. It provides a comprehensive and well-balanced treatment of its theme.